Therapists’ experiences with providing guided internet-delivered cognitive behavioral therapy for patients with mild and moderate depression: a thematic analysis - Børtveit, Line; Nordgreen, Tine; Nordahl-Hansen, Anders (Frontiers in Psychology, 2023)
Introduction Guided internet-delivered therapy has shown promising results for patients with mild and moderate depressive disorder, but several challenges with the format have been reported. The aim of this qualitative study was to investigate therapists’ experiences providing guided internet-delivered cognitive behavioral therapy for patients with mild and moderate depression. Material and methods Twelve therapists were interviewed, and the interviews were analyzed using reflexive thematic analysis. Results and conclusion Three themes were created: (1) For the right person, at the right time. This theme is about therapists’ experiences appointing patients to the program. It is challenging to predict which patients will benefit from it, and it is not the right option for all patients. (2) It is not like chatting on Facebook. The second theme was about the experiences with demands on clinics, therapists and patients that must be considered. The internet-delivered treatment should not be viewed as a simple treatment option, and the value of having contact with the patients during treatment was emphasized. (3) It is like a railroad, but without the switches. This theme was about the experiences with how the treatment content was conveyed to the patients, how the therapists expressed concerns with the usability of the program and the reported need for more possibilities in tailoring treatment for each patient.